Declining disease burden of HCC in the United States, 1992–2017: A population‐based analysis. Issue 3 (10th February 2022) - Han, Jianglong; Wang, Bin; Liu, Wenmin; Wang, Shijie; Chen, Ruyan; Chen, Mingkai; Fu, Zhenming
Abstract: Background and Aims: The incidence of HCC has recently been consistently reported to decline in the United States. However, decreased overall mortality of HCC has just been suggested and needs further examination. Approach and Results: Using data from the Surveillance, Epidemiology, and End Results databases, we assessed HCC incidence, incidence‐based mortality (IBM), and 1‐year survival rates from 1992 through 2017 in the United States. These secular trends were analyzed using the National Cancer Institute's Joinpoint Regression Program. Age‐period‐cohort analyses were performed to address underlying reasons for the observed temporal trends. The incidence and mortality of liver cancer in the United States by different etiologies were acquired from the Global Burden of Disease study (1990–2019) as a likely validation set. Joinpoint and age‐period‐cohort analyses were performed by etiologies. The incidence rates of HCC increased during 1992–2011 and sharply decreased thereafter by −2.3% annually (95% CI: −3.5% to −1.1%). IBM peaked in 2013 (age‐standardized mortality rate: 6.98 per 100, 000 person‐years) in the US population. IBM started to decrease significantly in 2013 by −3.2%/year (95% CI: −5.4% to −1.1% per year) after a continuous increase of 3.5% annually during 1993–2013. Overall, the 1‐year survival of HCC improved from 21.4% to 56.6% over the study period. However, the highest HCC incidence and mortality risk for patients aged 60–69 and born between 1952–1957 were found. Conclusions: We found significantly decreased overall HCC‐specific mortality since 2013 in the US population, along with decreased incidence and continuously improved survival. The changing etiologies, advances in screening and diagnosis, and improved treatment modality and allocation might all contribute to the downward trends of the disease burden of HCC in the United States. Abstract :